Muscular imbalance in elite handball players - practical consequences with respect to the prevention of injuries - Pieper, H. G.; Krödel, A.; Quack, G. (1998)
INTRODUCTION: Muscular imbalances are defined as a disproportion between the muscles that mainly function as stabilizers (postural muscles) and those mainly serving to induce motion (phasic muscles). Numerous studies have shown a high amount of muscular imbalance in athletes, some of them relating sport-specific imbalances to sport-specific injuries. METHODS: In order to investigate the influence of muscular imbalances on the development of typical sport-specific lesions in outstanding handball players, 42 male players from the top German handball division (1st Bundesliga), as well as 15 male and 12 female members of the German National Handball Team, were examined orthopedically. Especially using Janda`s "Functional Muscular Diagnostics", specific muscular imbalances were found. RESULTS: 37% of the male athletes reported chronic back problems, and 32% suffered from recurrent shoulder pain. Clinical examination revealed frequent cases of muscular shortening and weakness, mainly occurring in the pelvic region, as well as the shoulder. As far as back pain is concerned, handball players exhibiting clinical symptoms also demonstrate more muscular imbalances in the lower back - pelvis - hip region as compared to those not suffering from lumbar problems. Handball players suffering from shoulder pain have markedly more muscular imbalances of the shoulder girdle as compared to those who did not report any problems. CONCLUSIONS: The typical distribution of muscular shortening (especially of the hamstrings and the iliopsoas) and muscular weakness (abdominal and gluteal muscles, erector spinae lumbalis) can adversely affect the statics of the pelvic region. The resulting hyperlordosis is increased by certain training techniques, i.e., throwing medicine balls, which can lead to a segmental instability of the lumbar spine, thus contributing to chronic back pain. Muscular imbalances of the shoulder girdle may result in the use of improper throwing techniques, because due to muscular shortness of the major pectoral the amount of scapular adduction and depression is decreased. The shoulder thus being kept in constant protraction, the anterior joint capsule and the rotator cuff are subjected to pathological strain in every throwing motion of the arm, thus causing gleno-humeral instability and secondary impingement syndrome of the rotator cuff. The clinical significance of these muscular imbalances and their influence on the occurrence of sport-specific lesions will be discussed.